Effect of Organic and Inorganic Nutrition on Fertility Status of Soil and Yield of Vegetable Cowpea - Kanwar, Annu; Sharma, S R (Annals of Arid Zone, 2016)
A field experiment was conducted during kharif, 2012 on loamy sand soil, to study the effect of organic and inorganic nutrition on fertility status of soil and yield of vegetable cowpea [Vigna unguiculata (L.) Walp.] var. RCV-7. The treatments consisted four organic manure (control, FYM @ 10 t ha-1, vermicompost @ 5 t ha-1 and poultry manure @ 5 t ha-1) and five levels of inorganic nutrients (control, elemental sulphur @ 20 kg ha-1, elemental sulphur @ 20 kg ha-1 + ammonium molybdate @ 1.0 kg ha-1, elemental sulphur @ 20 kg ha-1 + ammonium molybdate @ 1.0 kg ha-1 + ferrous sulphate @ 50 kg ha-1, elemental sulphur @ 20 kg ha-1 + ammonium molybdate @ 1.0 kg ha-1 + ferrous sulphate @ 50 kg ha-1 + zinc sulphate @ 25 kg ha-1). The experiment was laid out in randomized block design and replicated thrice. The levels of available nitrogen, phosphorus, potassium, sulphur, molybdenum, iron and zinc in soil at crop harvest were maximum and significantly higher under vermicompost @ 5 t ha-1 (V5) over control. While significantly maximum organic carbon 0.278% was recorded with the application of FYM @ 10 t ha-1 (F10) and under the M3 (S + Mo + Fe). Under mineral nutrients treatments (M0-M4), the maximum available N, P, K, S, Mo, Fe and Zn in soil were recorded with the application of S + Mo + Fe + Zn (M4). The results revealed that the application of vermicompost @ 5 t ha-1 and combined application of S + Mo + Fe were found significantly superior in increasing the green pod yield of cowpea over control. Key words: Mineral nutrient, organic manure, green pod yield, cowpea.